PERAN KOMUNIKASI ANTAR BUDAYA TERHADAP ADAPTASI MAHASISWA PERANTAU DI SEKOLAH TINGGI ILMU ADMINISTRASI AMUNTAI - Noorrahman, Mohammad Fajar (TASHWIR, 2023)
The phenomenon of student exchange and migrant students is becoming increasingly common. Students who choose to continue their studies outside the region are not only faced with academic demands, but are also expected to be able to adapt to new social and cultural environments. The adaptation process involves the involvement of intercultural communication, where students must be able to interact with the local community. Therefore, this adaptation is very necessary to be able to adapt to the new environment. This research uses a quantitative method where samples are drawn using a purposive sampling technique. The research subjects were 236 students of STIA Amuntai semester 1 with migrant student status. The instruments used were adaptation and intercultural communication. Based on the results of the person product moment correlation analysis, it is known that the correlation coefficient is r = -0.425, which means there is a significant relationship between Intercultural Communication and adaptation with the direction of the relationship between the two variables being positive, which means that the higher the Intercultural Communication, the higher the adaptation. The effective contribution of Intercultural Communication to adaptation is 18.06%, while the other 81.94% of the contribution is influenced by other variables. Keywords:. Intercultural Communication, Adaptation, Domestik Student From Different Cities